Manajemen Inovasi Pendidikan Berorientasi Mutu pada MI Wahid Hasyim Yogyakarta - Sofanudin, Aji (IAIN Ponorogo, 2016)
Â This study aimed to explore the education innovation management with quality-oriented inMadrasah Ibtidaiyah Wahid Hasyim Yogyakarta that illustrated the importance of education in accordance with the learner learning developments and demands for innovation. Quality-oriented education innovation is an idea, practice, object, as well as new method in the field of education to achieve educational goals and solve educational problems. The aforementioned idea, practice, and new method are things that have been already established, run, and practiced in daily based management processes within the framework of improving the quality of education. By using the qualitative approach with case study, this researchrevealedvarieties or types of innovation that have been practiced in MI Wahid Hasyim Yogyakarta including (1) curriculum, (2) human resources, and (3) learning innovation. Therefore, it can be summed up that if education is a means to build human being with good personality, it must be ready to respond the change of time itself, so that innovation in the field of education is a must.ØØ§ÙÙ ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¯Ø±Ø§Ø³Ø© Ø¥Ø¯Ø§Ø±Ø© Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¹Ø§Øª Ø§ÙØªØ±Ø¨ÙÙØ© Ø¨ÙØ¯Ù Ø§ÙØ¬ÙØ¯Ø© ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ© ÙØ§ØØ¯ ÙØ§Ø´Ù ÙÙØºÙØ§ÙØ±ØªØ§ Ø§ÙØªÙ ØªØµÙÙØ± Ø£ÙÙ ÙØ© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙÙ ÙØ§Ø³Ø¨Ø© Ø¨Ù Ø±Ø§ØÙÙØ§ ÙÙ ØªØ·ÙÙØ¨Ø§Øª Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¹Ø§Øª. ÙØ§ÙØ¥Ø¨ØªØ¯Ø§Ø¹Ø§Øª Ø§ÙØªØ±Ø¨ÙÙØ© Ø¨ÙØ¯Ù Ø§ÙØ¬ÙØ¯Ø© ÙÙ Ø§ÙØ¢Ø±Ø§Ø¡ ÙØ§ÙØªØ·Ø¨ÙÙØ§Øª ÙØ§ÙÙ ÙØ¶ÙØ¹Ø§Øª ÙØ§ÙØ·Ø±Ù Ø§ÙØ¬Ø¯ÙØ¯Ø© ÙÙ Ù Ø¬Ø§Ù Ø§ÙØªØ±Ø¨ÙØ© ÙÙÙØµÙÙ Ø¥ÙÙ Ø£ÙØ¯Ø§Ù Ø§ÙØªØ±Ø¨ÙØ© ÙØÙÙ Ø§ÙÙ Ø´Ø§ÙÙ Ø§ÙØªØ±Ø¨ÙÙØ©. ÙØ°Ù Ø§ÙØ¢Ø±Ø§Ø¡ ÙØ§ÙØªØ·Ø¨ÙÙØ§Øª ÙØ§ÙØ·Ø±Ù ÙÙ Ø§ÙÙ Ø¹Ù ÙÙØ© ÙÙ ÙÙÙ ÙØ§Øª Ø§ÙØ¹Ù ÙÙØ© Ø§ÙØ¥Ø¯Ø§Ø±ÙØ© ÙÙ Ø¶ÙØ¡ ØªØ±ÙÙØ© Ø¬ÙØ¯Ø© Ø§ÙØªØ±Ø¨ÙØ©.Â ÙØµÙ ÙØ°Ø§ Ø§ÙØ¨ØØ« â Ø¨Ø§ÙÙ Ø¯Ø®Ù Ø§ÙÙÙØ¹Ù â Ø¥ÙÙ Ø§ÙÙØªÙØ¬Ø© ÙÙ ÙØ¬ÙØ¯ ØªÙÙÙØ¹ Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¹Ø§Øª Ø§ÙÙ Ø·Ø¨ÙÙ ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ© ÙØ§ØØ¯ ÙØ§Ø´Ù ÙÙØºÙØ§ÙØ±ØªØ§ ÙÙØØªÙÙ Ø¹ÙÙ : 1)Â Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¹Ø§Øª ÙÙ Ø§ÙÙ ÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³ÙØ 2) Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¹Ø§Øª ÙÙ Ø§ÙÙ ÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙÙØ©Ø 3) ÙØ§ÙØ§Ø¨ØªØ¯Ø§Ø¹Ø§Øª ÙÙ Ø§ÙØªØ¹ÙÙÙ . Ø¨ÙØ°Ø§ ÙÙ ÙÙ Ø£Ù ÙÙØ¤ÙÙØ¯ Ø¥Ø°Ø§ ÙØ§ÙØª Ø§ÙØªØ±Ø¨ÙØ© ÙØ³ÙÙØ© ÙØªÙÙÙÙ Ø§ÙØ´Ø®ØµÙØ© Ø§ÙØ¨Ø§Ø±Ø²Ø© Ø§ÙÙ ØªÙÙÙÙØ©Ø ÙØ¥Ù Ø§ÙØªØ±Ø¨ÙØ© ÙØ§Ø¨Ø¯Ù Ø£Ù ØªÙÙÙ Ù Ø±ÙØ© ÙÙ Ø³ØªØ¹Ø¯Ø© ÙØ§Ø³ØªØ¬Ø§Ø¨Ø§Øª Ø£ÙÙØ§Ø¹ Ø§ÙØªØ¬Ø¯ÙØ¯Ø§Øª ÙØ§ÙØªØºÙÙØ±Ø§Øª ÙÙ ÙØ°Ø§ Ø§ÙØ¹ØµØ± ØØªÙ ØªÙÙÙ Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¹Ø§Øª ÙÙ Ø¹Ø§ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø£Ù Ø± ÙØ§Ø¨Ø¯ Ù ÙÙ.Â